Poster #27 - One Health surveillance for influenza A viruses in Vietnamese live bird markets from January 2019 to April 2021 - Tung D. Dao; Coleman, K.K.; Vuong N. Bui; Anh N. Bui; Long H. Tran; Quy D. Nguyen; Son T. Than; Pulscher, L.A.; Marushchak, L.V.; Robie, E.R.; Hung Nguyen-Viet; Phuc Pham-Duc; et al. (Elsevier, 2025)
Background: The recent detections of H5N1 viruses among avian and mammalian species worldwide highlight the panzootic nature of influenza A viruses. There is specific concern that some influenza A viruses, such as H5N1, which are more generalist in nature and may be more prone to crossing the species barrier, causing disease in humans. Active surveillance for influenza A viruses among poultry, humans, and their shared environment is paramount to understanding their transmission potential and provides information on currently circulating avian strains.